Co-SBA-15 for heterogeneous oxidation of phenol with sulfate radical for wastewater treatment - Shukla, Pradeep; Sun, Hongqi; Wang, Shaobin; Ang, Ha Ming; Tade, Moses (Elsevier BV, 2011)
Mesoporous silica SBA-15 supported cobalt catalysts were prepared by co-condensation during SBA-15 synthesis, using three different Co(II) precursor salts, chloride (Cl), acetate (Ac) and nitrate (N). The physicochemical properties of the catalysts were characterized by several techniques, such as XRD, SEM (EDS), TEM, and FT-IR. It was found that Co3O4 was formed in SBA-15 and would effectively activate peroxymonosulfate to produce sulfate radicals for phenoloxidation in heterogeneous solutions. The Co precursors affected the physicochemical property, activity and stability of the catalysts. In heterogeneous reactions, the effects of catalyst loading, peroxymonosulfate concentration and reaction temperature on phenol degradation were investigated. The heterogeneousphenol degradation reactions followed zero order kinetics and the activation energies were 81.4, 67.4 and 67.4 kJ/mol for Co/SBA-15-Cl, Co/SBA-15-Ac, and Co/SBA-15-N, respectively.